Effects of nature-based mindfulness training on resilience/symptom load in professionals with high work-related stress-levels: findings from the WIN-Study - Luecke, Caroline; Braumandl, Sylvia; Becker, Bernhard; Moeller, Sebastian; Custal, Christina; Philipsen, Alexandra; Mueller, Helge H. O. (Mental Illness, 2019)
Purpose - The levels of work-related stress and the incidence rates of subsequent related illnesses are increasing in our society, leading to high individual and socioeconomic burdens. Mindfulness training has been shown to be an effective method of improving stress resilience. This paper aims to investigate the efficacy of nature-based mindfulness training in professionals with high levels of work-related stress.
CRIS-Team WoS Importer:2020-04-17